Evaluating the baseline survival outcomes of the "six Global Initiative for Childhood Cancer index cancers" in Africa. (3rd April 2023) - van Heerden, Jaques; Balagadde-Kambugu, Joyce; Angom, Racheal; Lusobya, Rebecca Claire; Chantada, Guillermo; Desjardins, Laurence; Fabian, Ido Didi; Israels, Trijn; Paintsil, Vivian; Hessissen, Laila; Diouf, Mame Ndella; Elayadi, Moatasem; et al.
Abstract: Limited survival data for the six Global Initiative for Childhood Cancer (GICC) priority cancers are available in Africa. Management of pediatric malignancies in Africa is challenging due to lack of resources, setting-specific comorbidities, high rates of late presentation and treatment abandonment. Reporting of outcome data is problematic due to the lack of registries. With the aim of evaluating the feasibility of baseline outcomes for the six index cancers, we present a descriptive analysis of respective survival rates in Africa. The survival rates were between 18% (lower middle-income countries) to 82.3% (upper middle-income countries) for acute lymphoblastic leukemia, between 26.9% (low-income countries) to 77.9% (upper middle-income countries) for nephroblastoma, between 23% (low-income countries) to 100% (upper middle-income countries), for retinoblastoma, 45% (low-income countries) to 95% (upper middle-income countries) for Hodgkin lymphoma and 28% (low-income countries) to 76% (upper middle-income countries) for Burkitt lymphoma. Solutions to improve survival rates and reported outcomes include establishing and funding sustainable registries, training and to actively include all countries in consortia from different African regions. Highlights: Continental differences in childhood cancer management such lack of resources, setting-specific comorbidities, high rates of late presentation and treatment abandonment, present challenges to the achievement of Global Initiative for Childhood Cancer goals. The available data registries do not adequately inform on the true incidences and outcomes of childhood cancers in Africa. The pathophysiology of some childhood cancers in Africa are associated with high-risk prognostic factors. Outcomes can be improved by greater regional collaboration to manage childhood cancer based on local resources and tumor characteristics. Some individual countries have reached the Global Initiative for Childhood Cancer goals for single cancers and it should be possible for more African countries to follow suit.